Effects of p-type-metal-doping (Ba, Cs, and Y) of the compact-TiO2 electron transporting layer on the photovoltaic properties of n-i-p perovskite solar cells - Nwankwo, U.; Nkele, Agnes Chinecherem; Arendse, Christopher Joseph; Ozoemena, Kenneth Ikechukwu; Ekwealor, Azubike B.C.; Jose, Rajan; Mǎaza, Maalik M.; Ezema, Fabian Ifeanyichukwu (Springer, 2023)
Tailoring of charge transport properties of the electron transport layer (ETL) in solution-processible solar cells is continuously addressed not only for the performance enhancements in perovskite solar cells but also in various other applications in nanotechnology. In this work, three p-type dopants: barium, cesium (Cs), and yttrium (Y) with varying crystal radii and charges are doped in the titanium dioxide (TiO2) material so as to modify the electrical and optical properties of the ETL. The pure and doped TiO2 films were prepared by spin-coating a sol–gel precursor and their effects on the crystal structure, morphology, optical, electrical and photovoltaic properties of the perovskite solar cells were studied and reported. Among them, Y-doped TiO2 with similar crystal radii as that of the host titanium atom showed an enhanced photo-conversion efficiency mainly contributed by enhanced open circuit voltage and fill factor. The power conversion efficiency (PCE) for the perovskite absorber layer on Cs- and Y-doped TiO2 show the maximum PCE of 2.81 and 4.50% respectively. These are encouraging results for optimizing the yttrium doping level and fabrication conditions to further push the performance indicators of PSCs.